2020
DOI: 10.5114/jcb.2020.100379
|View full text |Cite
|
Sign up to set email alerts
|

Biological dose summation of external beam radiotherapy for the whole breast and image-guided high-dose-rate interstitial brachytherapy boost in early-stage breast cancer

Abstract: Purpose To develop an alternative method for summing biologically effective doses of external beam radiotherapy (EBRT) with interstitial high-dose-rate (HDR) brachytherapy (BT) boost in breast cancer. The total doses using EBRT boost were compared with BT boost using our method. Material and methods Twenty-four EBRT plus interstitial HDR-BT plans were selected, and additional plans using EBRT boost were created. The prescribed dose was 2.67/40.05 Gy to whole breast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…As a boost after external beam radiotherapy, only Fröhlich et al. ( 79 ) combined interstitial multicatheter brachytherapy (3 × 4.75 Gy) with tangential beam WBI (15 × 2.67-Gy accelerated fractionation), showing that brachytherapy achieved a higher dose to the target with equal sparing of OARs in comparison to percutaneous treatment of both series, which is consistent with our observations, albeit for a normally fractionated dose concept.…”
Section: Discussionsupporting
confidence: 90%
“…As a boost after external beam radiotherapy, only Fröhlich et al. ( 79 ) combined interstitial multicatheter brachytherapy (3 × 4.75 Gy) with tangential beam WBI (15 × 2.67-Gy accelerated fractionation), showing that brachytherapy achieved a higher dose to the target with equal sparing of OARs in comparison to percutaneous treatment of both series, which is consistent with our observations, albeit for a normally fractionated dose concept.…”
Section: Discussionsupporting
confidence: 90%
“…Fröhlich et al used deformable image registration to combine volumetric modulated arc therapy and high-dose rate (HDR) brachytherapy dose contributions for 25 patients with intermediate- and high-risk prostate cancer. 34 The authors demonstrated superior BED of brachytherapy boost versus external beam boost but did not examine clinical toxicity. Moulton et al summed 4-field 3D conformal dose distributions with HDR for 118 patients with prostate cancer and found significant correlations between dose strata and GI toxicity such as rectal bleeding and stool frequency.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with bulky unresectable tumors, EBRT alone may not provide adequate loco-regional control [14]. Fröhlich et al [15] demonstrated that EBRT plus ISBT after breast surgery allowed for delivery of higher doses compared with EBRT alone.…”
Section: Discussionmentioning
confidence: 99%